A study on clinical outcome of obstructed labour - Indra, .; N., Usharani; Bendigeri, Mumtaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Obstructed labour accounts for 8% of maternal mortality in developing countries. Obstructed labour is the single most important cause of maternal death and is one of the three leading causes of perinatal mortality with the case fatality rate of 87-100%. Methods: The 50 patients with prolonged labour and maternal distress with signs and symptoms of maternal exhaustion, dehydration, keto-acidosis, Bandl’s ring formed the study subjects. Results: Out of the 50 cases studied the still birth rate was 24% (12 cases). This was due to delay in the referring the cases from peripheral centers. Conclusions: Our peripheral hospital need appointment of qualified personnel and well trained staff, who can recognize any deviation from normal labour and recognize malpresentation and malposition at the earliest and refer such cases to higher centers.